Perencanaan Strategis SI/TI Pada PT. XYZ Menggunakan Metode Ward And Peppard Kota Tangerang - Kevin Nagashi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
XYZ is a manufacturing company engaged in the distribution of pulp and paper where PT. XYZ itself has implemented IS/IT to support the achievement of the company's vision and mission, but in its implementation, the system used is often not effective and efficient, so a strategic and structured system design is needed. The expected result of this research is to plan an IS/IT strategy so that the implementation of the system when running the company's business processes can be more effective and efficient. The technique used in this study is the ward and Peppard method which consists of: SWOT analysis, Value Chain analysis, PEST analysis, Internal and External Environmental Analysis of IS/IT using the Mc Farlan Strategic Grid approach and Information System recommendations in the form of a framework. The final result expected from this research is a recommendation for the development of an existing system/application as well as a recommendation for a new framework if needed. Where this recommendation is expected to be an answer to the problems faced by companies related to IS/IT.